2021
DOI: 10.21203/rs.3.rs-512919/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Association Between Non-Suicidal Self-Injury of Adolescents and the COVID-19: The Lesson We Should Notice

Abstract: Background: Non-suicidal self-injury (NSSI) in psychiatric hospitalized adolescents keeps growing after the outbreak of COVID-19. This study aims to explore the relationship between the pandemic and the NSSI among adolescents, focusing on the underlying reasons. Methods: Through the retrospective analysis of medical record data retrieved from the electronic medical record system from January 2016 to March 2021, 609 medical records of adolescents were obtained. The main potential influencing factors were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In this study, we not only discovered a dramatic increase in adolescents with NSSI behaviours during the pandemic but also examined the structural changes in NSSI risk factors over time. The results showed that family constitution, relationship with their parents, mobile phone overuse, and stressful learning had significant association with NSSI behaviours during the pandemic, which were distinguished from those before the pandemic (49).…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we not only discovered a dramatic increase in adolescents with NSSI behaviours during the pandemic but also examined the structural changes in NSSI risk factors over time. The results showed that family constitution, relationship with their parents, mobile phone overuse, and stressful learning had significant association with NSSI behaviours during the pandemic, which were distinguished from those before the pandemic (49).…”
Section: Discussionmentioning
confidence: 94%